The implicit manifestation of the phenomenon of linguistic aggression in Kazakhstani periodicals (On the example of the socio-political newspaper “Zhas Alash”) - Mukhanbetzhanova А.Р; Tapanova С.Е. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
Today, the phenomenon of aggression in communication is becoming more acute, and the problem of its scientific study is becoming urgent. Language aggression has a great impact not only on virtual communication, but also on interpersonal communication. Language aggression is widely used in the media and social networks. This phenomenon manifests itself in an open and implicit (hidden) form. It is difficult to determine the implicit form of linguistic aggression. It not only shapes public opinion and increases tension, but also affects the moral and social situation in the country. The study analyzes the phenomenon of linguistic aggression in the republican socio-political newspaper “Zhas Alash.” During the study of linguistic aggression in the newspaper “Zhas Alash”, implicit aggression was analyzed and the mechanisms of its impact on the reader were considered. The article provides links to research conducted by scientists from both foreign and domestic scientists. This allows for a deeper understanding of the nature and consequences of implicit linguistic aggression in the media sphere. The results obtained in the article emphasize the need to improve media literacy and develop effective strategies to reduce language aggression. In addition, this study is an important step towards clarifying how linguistic aggression negatively affects peace and mutual understanding in society.